Innovative Aspects Of Energy Resources Saving And Energy Efficiency - ABANNIKOV, VICTOR N.; KATKOVA, TATYANA V.; SABANCHIEVA, DINARA KH.; KAMCHATOVA, EKATERINA YU.; OSMONOV, OROZMAMAT M.; SHAROSHCHENKO, VLADIMIR S.; KOSNIKOV, SERGEY N. (The journal of contemporary issues in business and government, 2021)
The global stocks of energy resources are reducing with each year, and their extraction demands more and more investments. The authorities of the developed countries put lots of effort into the energy efficiency technologies development and their implementation into the life of society and business processes. The aim of this article is to consider the strategic prospects of “green” economic development and justify the central place of energy saving and energy efficiency in the system of business priorities for its innovative impact on production development, including the decrease of the final product price. The choice of case study countries – the USA, Canada, the EU, the UK, Japan, China, Korea, Singapore, Hong Kong, Taiwan, and Russia – allowed to present the diversity of approaches to energy efficiency and saving programs within different social and political cultures. The first part of the article is dedicated to the government programs on energy efficiency and energy saving which are used in many world countries in order not only to improve the environmental situation but also to make the enterprises develop their production technologies and use the energy resources rationally. The second part of the article is devoted to the new alternative sources of energy and the technologies that help to reduce energy use in the everyday life. The importance of building close interconnection of state policy for energy efficiency and innovative business development as the source of opportunities for conducting technological modernization of industrial production focused on the use of advanced energy-saving technologies is stressed.